DEVELOPMENT CHARACTERISTICS OF DAILY LIVING SKILLS IN 8–9-YEAR-OLD CHILDREN WITH AUTISM SPECTRUM DISORDER - Ayaulym Baktygalieva; Akbota Autayeva (Research Retrieval and Academic Letters, 2026)
This article examines the development characteristics of daily living skills in 8–9-year-old children with Autism Spectrum Disorder (ASD) from a theoretical perspective. The relevance of the study is determined by the increasing focus on life skills development within the modern special education system, as well as the significant role of daily living skills in the social adaptation of children with ASD. It analyzes the level of development of daily living skills in this age group, the specific characteristics of their development, the difficulties encountered, and the reasons behind these challenges. Particular attention is paid to skills related to self-care, performing daily routines, and enhancing the level of independence. In addition, the key factors affecting the development of daily living skills in children with ASD are identified, and their interrelationships are theoretically substantiated.